2015
DOI: 10.1200/jco.2015.62.4304
|View full text |Cite
|
Sign up to set email alerts
|

Time to Definitive Failure to the First Tyrosine Kinase Inhibitor in Localized GI Stromal Tumors Treated With Imatinib As an Adjuvant: A European Organisation for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group Intergroup Randomized Trial in Collaboration With the Australasian Gastro-Intestinal Trials Group, UNICANCER, French Sarcoma Group, Italian Sarcoma Group, and Spanish Group for Research on Sarcomas

Abstract: This study confirms that adjuvant imatinib has an overt impact on RFS. No significant difference in IFFS was observed, although in the high-risk subgroup there was a trend in favor of the adjuvant arm. IFFS was conceived as a potential end point in the adjuvant setting because it is sensitive to secondary resistance, which is the main adverse prognostic factor in patients with advanced GIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 18 publications
(2 reference statements)
4
122
2
1
Order By: Relevance
“…Most GISTs have a gain-offunction mutation of the c-kit or platelet-derived growth factor receptor alpha (PDGFRA) genes in ICC, which results in ligand-independent activation of the receptors and consequential tumor progression (3)(4)(5). Although surgery is the most effective treatment for resectable primary GISTs without metastasis, post-operative recurrence or metastasis occurs in nearly 30% of patients within 3 years after complete resection in the absence of adjuvant therapy, and those metastatic GISTs are difficult to cure with surgery alone (6)(7)(8)). …”
Section: Introductionmentioning
confidence: 99%
“…Most GISTs have a gain-offunction mutation of the c-kit or platelet-derived growth factor receptor alpha (PDGFRA) genes in ICC, which results in ligand-independent activation of the receptors and consequential tumor progression (3)(4)(5). Although surgery is the most effective treatment for resectable primary GISTs without metastasis, post-operative recurrence or metastasis occurs in nearly 30% of patients within 3 years after complete resection in the absence of adjuvant therapy, and those metastatic GISTs are difficult to cure with surgery alone (6)(7)(8)). …”
Section: Introductionmentioning
confidence: 99%
“…Second, only 8.7% of patients were administered adjuvant therapy in this study, even though 67.0% of the patients were categorized as high-risk. Some studies have shown that 1 or 2 years of adjuvant imatinib significantly improved recurrence-free survival (RFS) after complete resection compared to placebo [23,24]. Additionally, 3 years of adjuvant imatinib therapy has been shown to improve RFS significantly better than just 1 year of the therapy in high-risk GIST patients, and its administration is now recommended in high-risk patients [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Das progressionsfreie Überleben in den einzelnen Studien ist sehr lang. Allerdings ist die Interpretation dieser Ergebnisse im Vergleich zu Serien mit primär operierten Patienten schwierig, da die Indikation zur zusätzli-chen postoperativen Imatinib-Therapie, die einen erheblichen Einfluss auf das Auftreten eines Rezidives hat [16,17], in den einzelnen Studien heterogen gestellt wurde.…”
Section: Nicht Metastasierte Gist -Primäre Resektion Vs Neoadjuvanteunclassified